Sanditon Season one [videorecording (DVD)] - Clarke, Crystal; Spencer, Charlotte; Ashfield, Kate; Austen, Jane, 1775-1817 (Masterpiece , PBS, 2020)
Tom Parker is obsessed with turning the sleepy seaside village of Sanditon into a fashionable health resort, enlisting the backing of local bigwig Lady Denham. Through a mishap, Tom makes the acquaintance of the Heywoods and invites their eldest daughter, Charlotte, for an extended stay at Sanditon. Meanwhile, Lady Denham, a widow, is playing matchmaker for her destitute nephew, Sir Edward, who is determined to seduce Lady Denham's ward, Clara.